Effects of capture, shearing, and release on the ecology and behavior of wild vicuñas - Arzamendia, Yanina (2012)
The goals of sustainable use of wildlife include minimizing long term deleterious impacts of management. We evaluated the ethoecological and demographic responses of wild vicuñas (Vicugna vicugna) to capture, shearing, and release in northern Argentina, as well as effects on behavior, by comparing captured and shorn versus non-captured animals for 2 yr after capture events. We observed subtle and short-term changes in the movement behavior of individuals, likely due to thermal and behavioral stress following capture. We did not observe changes in survival and birth rates, social organization, or distribution of animals following capture. Therefore, we concluded that the capture techniques used resulted in low impacts on the wild vicuña population.